The effect of plyometric training on central and peripheral fatigue in boys - Skurvydas, A.; Brazaitis, M.; Streckis, V.; Rudas, E. (International Journal of Sports Medicine, 2010)
The aim of this study was to investigate the effect of high-intensity plyometric training (PT) on central and peripheral fatigue during exercise performed at maximal intensity in prepubertal boys. The boys (n=13, age 10.3±0.3 years) performed continuous 2-min maximal voluntary contractions (MVC) before and after 16 high-intensity PT sessions (two training sessions per week, 30 jumps in each session, 20 s between jumps). The greatest effect of PT was on excitation-contraction coupling: twitch force increased by 323.2±210.8% and the height of a counter-movement jump increased by 36.7±11.7%, whereas quadriceps femoris (QF) muscle voluntary activation index, central activation ratio and MVC did not change significantly after PT. The thickness of QF increased by 8.8±7.9% after PT. Central fatigue increased significantly by about 15-20% after PT, whereas peripheral fatigue decreased significantly by about 10% during the 2-min MVC. Central fatigue and peripheral fatigue during the 2-min MVC were inversely related before PT, but this relationship disappeared after PT.